2001
DOI: 10.1161/hh2401.101066
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Annexin II Modulates Impaired Fibrinolytic Activity In Vitro and in Rat Carotid Artery

Abstract: Abstract-Fibrinolytic activity has been reported to be decreased in atherosclerosis. Recently, annexin II was identified as a coreceptor on endothelial cells for plasminogen and tissue plasminogen activator. In this study, we examined whether recombinant annexin II (rAN II) protein can modulate fibrinolytic activity on vascular endothelium in vitro and in vivo. Key Words: annexin II Ⅲ rat carotid artery Ⅲ thrombus V ascular endothelial cell luminal surfaces maintain a "thromboresistant status" by dynamic balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 24 publications
3
57
1
4
Order By: Relevance
“…Interestingly, there were no significant differences in ADC lesion volume at 180 min after stroke among groups B, C and D. These results are consistent with our previous observation that rAN II-promoted plasmin generation may have been saturated at higher concentrations (Ishii et al, 2001). …”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Interestingly, there were no significant differences in ADC lesion volume at 180 min after stroke among groups B, C and D. These results are consistent with our previous observation that rAN II-promoted plasmin generation may have been saturated at higher concentrations (Ishii et al, 2001). …”
Section: Discussionsupporting
confidence: 91%
“…We have previously shown that annexin 2 is attached to endothelial cells in a calcium-dependent manner and fibrinolytic activity disappears in the absence of calcium (Ishii et al, 2001). rAN II restored impaired fibrinolytic activity and sustained carotid flow when rAN II was present on the endothelium.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations